The Difficulties Facing by Student in Using Participle in Sentences - Zahari Amir Bin Ismani; Siska Simamora (Cendikia : Media Jurnal Ilmiah Pendidikan, 2021)
This study deals with the student’s difficulties in using participle in sentences. The purposes of the study were to find out whether or not the students found difficulties in using participle in sentence and to find out the type of difficulties they faced. The population of the study was students. In this sampling, all the population has equal chance to be selected for the sample. The total numbers of samples was 32 students. The instrument used to collect the data was multiple choice test. This research was conducted by applying the descriptive quantitative design. The reliability of the test is counted by using KR21 formula. The formula testing result showed that the reliability of the test was 0,84, it means that the test was very good. The percentage of the student’s errors is dominantly occured in descriptive adjectives from 800 item occurrences, there were 436 errors which categorized into 5 sub categories on the use of adjectives and adverbs with the suffix–ly. The finding showed that the students found some difficulties in using participle, they were: Present Participle (22,52 %), Past Participle (63,73 %) and Perfect Participle (33,52 %). Past Participle was regarded as the most difficult type for them, especially in using it after certain verbs and in replacing relative pronoun, and then followed by Perfect Participle. And the last was Present Participle especially in using in it replacing relative pronoun and after certain verb. The percentage of each difficulty was taken by dividing the wrong answer to the total correct answer of the test.